Improvement of Science Process Skills Through Development of Work Sheets Integrated by Terrarium Media Global Warming Materials - Dyah Ayu Fajarianingtyas (Indonesian Journal of Science and Education (IJOSE), 2020)
Science process skill is used as basic skill in learning of science, according to the real science include the aspects of attitude, process, product, and application as a whole skill. The purpose of this research is to know increase of students’ science process skill after used worksheet which is developed. The kind of this research is development research adopt development model of Dick and Carey, with using descriptive research methods. The subject of this research is the VII grade students at SMPN 2 Sumenep academic year 2017/2018. The result of data testing shows that students’ science process skill increase with N-gain average 0,7 high criteria. Worksheet was chosen to be developed as learning material in this research, because worksheet can support the effectivity of learning based science process skill. Worksheet that had been developed can be used as learning material to increase students’ science process skill through observation by using media of terrarium.